2020
DOI: 10.33151/ajp.17.834
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Scoping Review Reporting within Paramedicine: A Scoping Review

Abstract: Aim This study aimed to examine the quality of published paramedic scoping reviews against pre-existing frameworks to assess the extent to which they fulfil the requirements of this methodological approach. Subsequently, recommendations will be presented regarding improvements for future paramedic scoping reviews. Methods A scoping review was conducted guided by the PRISMA Extension for Scoping Reviews. A literature search was performed in six electronic databases as well as the grey literature to identify pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Scoping reviews are an increasingly used methodology for reviewing literature when the strict nature of a systematic review is unlikely to yield results relevant to the aims of the review. 21 Arksey and O'Malley, 22 the first authors to propose the scoping review methodological framework, give four reasons where a scoping review may be of relevance: [23][24][25] but variations in the execution of scoping reviews exist. 21 A rigorous framework, such as the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews (PRISMA-ScR), 25 is recommended to ensure scientific rigour, reproducibility and transparency, ensuring scoping reviews meaningfully add to the literature.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scoping reviews are an increasingly used methodology for reviewing literature when the strict nature of a systematic review is unlikely to yield results relevant to the aims of the review. 21 Arksey and O'Malley, 22 the first authors to propose the scoping review methodological framework, give four reasons where a scoping review may be of relevance: [23][24][25] but variations in the execution of scoping reviews exist. 21 A rigorous framework, such as the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews (PRISMA-ScR), 25 is recommended to ensure scientific rigour, reproducibility and transparency, ensuring scoping reviews meaningfully add to the literature.…”
Section: Methodsmentioning
confidence: 99%
“…21 Arksey and O'Malley, 22 the first authors to propose the scoping review methodological framework, give four reasons where a scoping review may be of relevance: [23][24][25] but variations in the execution of scoping reviews exist. 21 A rigorous framework, such as the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews (PRISMA-ScR), 25 is recommended to ensure scientific rigour, reproducibility and transparency, ensuring scoping reviews meaningfully add to the literature. 21 As such, a six-stage framework, as shown below, described by Levac et al 23 was used in conjunction with the PRISMA-ScR checklist: 25 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Among paramedicine researchers, scoping reviews are an increasingly popular approach. 8 Consistent with this growth, scoping reviews are amongst the most common manuscripts submitted to Paramedicine, the official journal of the Australasian College of Paramedicine and the Paramedic Chiefs of Canada. However, the Editorial Board has identified considerable variation in methodological and reporting quality, a problem not unique to Paramedicine but also seen and documented in other healthcare disciplines.…”
mentioning
confidence: 93%
“…However, the Editorial Board has identified considerable variation in methodological and reporting quality, a problem not unique to Paramedicine but also seen and documented in other healthcare disciplines. 1,8 The aim of this editorial is to highlight recurrent areas of concern relating to methodology and reporting of scoping review manuscripts as identified by the Editorial Board and provide guidance to paramedicine researchers specific to the requirements and expectations of Paramedicine .…”
mentioning
confidence: 99%